(untitled) (Indonesian Journal of Civil Engineering Study, 2025)
The Rawalumbu River is located in Rawalumbu District, Bekasi City. High population density, limited land, and poor drainage conditions have reduced water absorption areas, leading to erosion and an increased risk of flooding. This study aims to determine the design discharge and river dimensions required to prevent flooding. Hydrological analysis of planned rainfall was conducted using the Normal, Gumbel Type I, Log Pearson III, and Log Normal methods. The design flood discharge was calculated using the Nakayasu and Snyder Unit Hydrograph methods, while hydraulic analysis was conducted using the HEC-RAS application. Simulation results indicate that flooding occurs under existing conditions but not with the proposed design. It is necessary to increase river dimensions and levee elevation to accommodate larger discharge volumes. Each river section has different cross-sectional dimensions, with the main river featuring a base width of 20 meters, a height of 4 meters, and varying elevations at the upstream and downstream ends. The tributary has smaller dimensions, with a base width of 15 meters and a height of 4 meters. The Rawalumbu River is designed to accommodate a 25-year return period discharge of 81.24 m³/s, with the expectation that it will effectively prevent flooding.